폐결핵 환자의 입원기간동안 영양상태 변화 연구 - 유현재(You Hyunjai); 김양하(Kim Yangha) (Hanʼguk yongyang hakhoe chi, 2009)
This study was conducted to evaluate the change of nutritional status and to analyze related factors in hospitalized tuberculosis (TB) patients during their hospitalization. The subjects were 398 men patients (mean age: 47.3 ${±}$ 14.4 y) who had hospitalized more than 3 months at TB hospital located in Seoul. The anthropometric and blood biochemical indices were measured, and dietary intakes were assessed. At the time of admission the body weight of subjects was about 76% of the average body weight of Korean men with same age, Body mass index (BMI) of subjects was 18.5 kg/$m^2$, and 53.8% of subjects were under weight status. Average level of blood hemoglobin and hematocrit of subjects was lower than the normal value. After 3 months of hospitalization period, the body weight and body mass index were significantly increased compared to admission by 3.9 kg (7.41%) and 1.4 kg/$m^2$ (7.61%)(p < 0.001), respectively. Blood levels of hemoglobin, hematocrit, albumin, and total protein were also significantly increased after 3 months of hospitalization period compared to admission (p < 0.001). The increment in the body weight and blood indices was significantly higher in below 29 years group than over 60 years group (p < 0.05). The increment in the body weight and body mass index was significantly higher in the under-body weight group compared to the normal-body weight group (p < 0.05). In conclusion the body weight and body mass index of subjects were significantly increased after 3 months of hospitalization period, and the age and body weight of subjects at admission were supposed to influence the degree of change in the nutritional status. 본 연구는 폐결핵으로 입원한 환자들의 입원 기간 동안의 영양상태 변화를 평가하고 이에 미치는 영향 요인들을 분석하고자 하는 목적으로 진행 되었다. 1) 조사대상자의 평균 연령은 47.3세였으며, 폐결핵 유병기간은 평균 11.2개월로 대상자의 58.5%가 유병기간 3개월 이하의 초기발병환자였고, 대상의 73.1%가 처음 입원한 환자였다. 입원기간은 평균 112.4일로 약 4개월 정도의 입원치료기간을 갖는 것으로 나타났다. 2) 입원 시점의 영양 상태는 평균 신장 168.9 cm, 체중 52.6 kg으로 한국인 성인남성의 표준 키, 체중과 비교하여 키는 비슷하였으나 체중은 성인 남성 표준치의 약 76%에 불과하였으며, 체질량지수 역시 평균 18.4 kg/$m^2$로 전체 대상의 53.8%가 저체중 상태였다. 생화학적 지표로 혈중 헤모글로빈과 헤마토크릿은 각각 12.3 g/dL, 35.4%로 정상 수치보다 낮았고, 혈청알부민 수치는 3.5 g/dL로 경계치 수준이었으며, 총 단백질 수치는 7.2 g/dL로 정상범위였다. 3) 평균 체중은 입원 시 52.6 kg에서 입원 3개월 후 56.5kg으로 유의적으로 증가하였고, 체질량지수 역시 유의적으로 증가하였다 (p < 0.001). 혈중 헤모글로빈, 헤마토크릿, 혈청알부민, 총 단백질의 수치 역시 모두 입원 시점보다 유의적으로 증가하여 (p < 0.001) 개선되는 결과를 보였다. 4) 입원기간 중 체중 및 생화학적 지표의 변화량을 각 요인에 따라 분석한 결과 연령이 증가할수록 그 증가량은 감소하여, 특히 60세 이상 연령의 환자들의 증가량은 29세 이하와 30대 환자에 비교하여 유의적으로 낮았고, 입원 시의 체질량지수가 18.5 kg/$m^2$ 미만인 저체중그룹의 증가량이 정상체중그룹보다 유의적으로 높았으며 입원기간 동안 식이섭취 정도가 보통 또는 양호한 그룹에서의 증가량이 섭취불량 환자그룹보다 유의적으로 높았다. 5) 연령이 낮은 그룹에서는 식사섭취가 양호한 환자의 비율이 높았고, 연령이 높은 그룹에서는 식사섭취가 불량한 환자의 비율이 높아 저 연령의 환자일수록 제공식사 섭취량이 높았다. 입원기간 동안의 식사섭취가 불량한 그룹은 식사섭취가 보통이거나 양호한 그룹과 비교하여 평균연령이 유의적으로 높았고, 유병기간은 짧았으며 입원기간이 긴 결과를 나타내었다. 본 연구 결과 폐결핵으로 입원하는 환자들의 입원시점의 영양 상태는 일반적으로 취약한 상태로 영양적 중재가 필요하며, 입원기간 동안의 영양상태의 변화는 환자의 연령과, 입원시점의 체질량지수, 입원기간 동안의 식이섭취 등과 관련이 있었다.